Uni-Messe: Unified Rule-Based Message Delivery Service for Efficient Context-Aware Service Integration - Takuya Nakata; Sinan Chen; Masahide Nakamura (Energies, 2022)
Rule-based systems, which are the typical technology used to realize context-aware services, have been independently implemented in various smart services. The challenges of these systems are the versatility of action, looseness, and the coding that is needed to describe the conditional branches. The purpose of this study was to support the realization of service coordination and smart services using context-aware technology by converting rule-based systems into services. In the proposed method, we designed and implemented the architecture of a new service: Unified Rule-Based Message Delivery Service (Uni-messe), which is an application-neutral rule management and evaluation service for rule-based systems. The core part of the Uni-messe proposal is the combination of a Pub/Sub and a rule-based system, and the proposal of a new event–condition–route (ECR) rule-based system. We applied Uni-messe to an audio information presentation system (ALPS) and indoor location sensing technology to construct concrete smart services, and then compared and evaluated the implementation to “if this then that” (IFTTT), which is a typical service coordination technology. Moreover, we analyzed the characteristics of other rule-based systems that have been serviced in previous studies and compared them to Uni-messe. This study shows that Uni-messe can provide services that simultaneously combine versatility, ease of conditional description, looseness, context independence, and user interface (UI), which cannot be achieved using conventional rule-based system services. By using Uni-messe, advanced heterogeneous distributed service coordination using rule-based systems and the construction of context-aware services can be performed easily.